Vacancy-like defects in nanocrystalline SnO2: influence of the annealing treatment under different atmospheres - Macchi, Carlos Eugenio (2018)
The study of electronic and chemical properties of semiconductor oxides is motivated by their several applications. In particular, tin oxide is widely used as a solid state gas sensor material. In this regard, the defect structure has been proposed to be crucial in determining the resulting film conductivity and then its sensitivity. Here, the characteristics of vacancy-like defects in nanocrystalline commercial high-purity tin oxide powders and the influence of the annealing treatment under different atmospheres are presented. Specifically, SnO2 nanopowders were annealed at 330 °C under three different types of atmospheres: inert (vacuum), oxidative (oxygen) and reductive (hydrogen). The obtained experimental results are discussed in terms of the vacancy-like defects detected, shedding light to the basic conduction mechanisms, which are responsible for gas detection.